THE BUCK STOPS … WHERE, EXACTLY? ON OUTSOURCING AND LIABILITY TOWARDS THIRD PARTIES - Daleen Millard; Monray Marsellus Botha (Obiter, 2021)
Modern-day commerce forces services providers to make use of outsourcing. Regardless of whether outsourcing is used for bona fide reasons such as to provide a better product at a better price or whether the outsourcer needs to dispose of troublesome employees or to limit his liabilities towards third parties, it is suggested that outsourcers should consider a number of issues when outsourcing. Conversely,in considering a liability issue, a court may also measure the conduct of a particular outsourcer in order to evaluate whether such outsourcer has acted bona fide and responsibly. Little research is available on outsourcing and the affect thereof on third-party liability. Although the LRA and CPA contains provisions on certain general aspects, it may be that industry-specific legislation regulates specific outsourcingagreements. This article attempts to reconcile these seemingly disjointed topics. The authors conclude that sound legal advice should be sought before outsourcing is considered in order to avoid possible problems associated with it as well as liability-related pitfalls.